Natural hazards, vulnerability and structural resilience: tsunamis and industrial tanks (2016)
The paper presents an integrated framework which deals with natural hazards (tsunamis), physical vulnerability modelling, risk of failure for industrial structures (metal structures) and structural resilience provided by plastic adaptation. Simplified models are proposed to describe the run-up and wave height attenuation in case of tsunamis. The results are calibrated in the case of important tsunamis having taken place in Asian region. The mechanical vulnerability of cylindrical metal tanks erected near the shoreline is also investigated. The fragility curves are then developed in order to describe the multimodal failure: overturning, rupture of anchorages and sliding, buoyancy, excessive bending effects or buckling. Corresponding fragility curves are developed under various conditions: height of tsunami waves, filling ratios and service conditions of the tanks, friction tank/ground as well as dimensions effects. Probabilistic description of the natural hazard and the fragility curves are presented. Sensitivity analysis is also performed in order to investigate the effect of various governing parameters. Furthermore, resilience concepts and metrics are proposed. Theoretical description of the damages and post-disaster recovery functions are discussed: plastic adaptation as well as elastic and plastic attractors.